ANALISIS PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA KEDAI KOPI LOKAL - Archie, Archie; Rita, Rita (Bajang Institute, 2025)
This study analyzes the influence of brand image, product quality, and price on consumer loyalty, with customer satisfaction as an intervening variable in local coffee shops in Jakarta. The research employs a quantitative method with a survey approach. Data were collected through questionnaires and analyzed using path analysis to examine the relationships between variables. The results show that brand image, product quality, and price each have a significant partial effect on customer satisfaction. Additionally, these three variables also directly influence consumer loyalty. Customer satisfaction plays a crucial role in enhancing loyalty and serves as an intervening variable in the relationship between brand image, product quality, and price with consumer loyalty. These findings provide implications for local coffee shop owners and managers in formulating more effective marketing strategies. Improving brand image, maintaining product quality, and offering competitive pricing can enhance customer satisfaction and ultimately strengthen consumer loyalty